AB0294 Lymphocyte Recovery after Methotrexate Discontinuation Relate To Spontaneous Regression of Mtx-Lpd in Ra Patients. (15th July 2016) - Kameda, T.; Dobashi, H.; Inoo, M.; Onishi, I.; Kurata, N.; Izumikawa, M.; Nakashima, S.; Shimada, H.; Ozaki, H.; Wakiya, R.; Kadowaki, N.
Abstract : Background: Rheumatoid arthritis (RA) patients have a high risk of onset of lymphoproliferative disorders (LPD). Especially, LPD develop in patients treated with methotrexate (MTX) is known as MTX-associated LPD (MTX-LPD). MTX-LPD is classified among the "immunodeficiency-associated lymphoproliferative disorders (ID-LPD)" as an "other iatrogenic ID-LPD" in the 2008 WHO Classification of Tumours of Haematopoietic and Lymphoid Tissues (1). We previously reported that MTX is an independent risk factor for LPD onset in Japanese RA patients (2). Characteristic of MTX-LPD is that MTX withdrawal possibly results in spontaneous regression of the LPD. Furthermore, there are some reports that the Epstein-Barr virus (EBV) infection is related to spontaneous regression of MTX-LPD. However, enough evidence about the relation with EBV infection and spontaneous regression of MTX-LPD is not presented. In addition, biomarker predicting a spontaneous regression of MTX-LPD has not been clarified. Objectives: We examined the clinical characteristics of MTX-LPD in Japanese RA patients and attempted to determine the predictive marker for spontaneous regression of MTX-LPD. Methods: We enrolled 33 RA patients who developed MTX-LPD from Kagawa Prefecture, Japan between June 2010 and December 2015. Patients were diagnosed according to American College of Rheumatology 1987 classification criteria, and treated with disease modifying antirheumatic drugs (DMARDs) including MTX. We divided into patients who were followed-up after the discontinuation of MTX alone (MTX withdrawal group) and patients who were performed chemotherapy after one month or more of the MTX discontinuation (chemotherapy group). The following differences between the two groups were examined: 1) serum LDH; 2) serum CRP; 3) sIL-2 receptor; 4) lymphocyte counts before and after MTX discontinuation; 5) hemoglobin; 6) histological findings related to LPD; 7) EBV association; 8) number of LPD lesions and 9) outcome. Results: There were 28 patients in the MTX withdrawal group and 5 patients in the chemotherapy group. Laboratory data such as LDH, CRP, sIL-2R, lymphocyte counts and hemoglobin showed no significant difference in two groups. Furthermore, there is no difference between two groups about EBV infection and number of LPD lesions. However, significant differences were found in the change ratio of lymphocyte between the two groups. Conclusions: We revealed that the change of lymphocyte before and after the MTX discontinuation relate to spontaneous regression of the MTX-LPD. This data suggest that the recover of lymphocyte after the MTX discontinuation may become a predictive marker for MTX-LPD treatment strategy. References: Swerdlow SH, Campo E, Harris NL, Jaffe ES, Pileri SA, Stein H, et al., WHO Classification of Tumours of Haematopoietic and Lymphoid Tissues. IARC Press, Lyon, 2008. Association of higher methotrexate dose with lymphoproliferative disorders onset in rheumatoid arthritis patients. Kameda T, Dobashi H, Miyatake N, Inoo M, Onishi I, Kurata N, Mitsunaka H, Kawakami K, Fukumoto T, Susaki K, Izumikawa M, Nakashima S, Shimada H, Takeuchi Y, Haba R, Mano S, Onishi H, Imataki O, Matsunaga T. Arthritis Care Res (Hoboken). 2014 Sep;66(9):1302–9. Disclosure of Interest: None declared